Analysis of effect of water body on temperature and humidity around a building using COMSOL - Tan, Cheryl (Nanyang Technological University, 2020)
In this study, the benefits of evaporative cooling effect from waterbody and temperature profile of a building exterior is analysed while setting realistic consideration such as wind, building parameters and surface area of waterbody. Various building shapes such as conical-roof, dome-roof and flat-roof building are also modelled to analyse the difference in their temperature distributions. COMSOL Multiphysics software is used to predict the temperatures and vapor concentration around the building and waterbody. The results show a 1 degree celcius drop in atmospheric temperature with the presence of waterbody and when coupled with wind velocity of 2m/s, 1.5m radius around the pool experience this cooling effect. Their highest temperature of the environment also decreases by 7.8 degree celcius.